Study on the establishment and implementation of sector budget after college merger - GE Xiang-fu (浙江大学学报. 农业与生命科学版)
During the course of college merging, the substantial combination of finance has attracted much attention from the public. However, sector budget plays a key role in the issue of finance after college merger. Linking the practical experience of the merger of Zhejiang University, this article expounds the essential tasks, establishment principles and ideas of sector budget subsequent to college merger, and puts forward specific measures to improve the establishment and management of sector budget.